The city of the future - Glazebrook, G.; Newman, Peter (Cogitatio, 2018)
© 2018 by the authors. Limiting global warming to 1.5 °C will require rapid decarbonisation of the world’s electricity and transport systems. This must occur against a background of continuing urbanisation and the shift to the information economy. While replacement of fossil fuels in electricity generation is underway, urban transport is currently dominated by petrol and diesel-powered vehicles. The City of the Future will need to be built around a different transport and urban paradigm. This article argues that the new model will be a polycentric city linked by fast electric rail, with local access based on autonomous “community”- owned electric cars and buses supplemented by bicycles, electric bikes and scooters, with all electricity generated from renewables. Less space will be wasted on roads and parking, enabling higher accessibility yet more usable public open space. Building the cities of the future will require national governments to accelerate local initiatives through appropriate policy settings and strategic investment. The precise way in which individual cities move into the future will vary, and the article illustrates how the transformation could work for Australian cities, like Sydney, currently some of the most car dependent in the world, using new financial and city partnerships.